PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 22 PADANG - Fitrahazzahra, Fellania (Jurnal Edukasi dan Penelitian Matematika, 2024)
Teachers can tell if their learning is effective based on learning outcomes. The problem of low learning outcomes was identified using data and observations from grade eight at SMPN 22 Padang. Learning outcomes are influenced by the learning materials used. Therefore, a solution was proposed to improve learning outcomes and student engagement through the use of Articulate Storyline 3-based interactive learning media. This study aimed to determine whether, compared to more conventional forms of teaching, interactive learning media actually improved student performance. There was a non-equivalent control group that only participated in the post-test in this quasi-experimental study. An essay-based posttest was administered as an evaluation. Based on the posttest results, it was found that using Articulate Storyline 3 interactive media had better learning outcomes. The fact that the P-value < α (0.044) supports the acceptance of the alternative hypothesis. So, it can be said that when they use the Articulate Storyline 3 interactive media compared to the conventional way to be better.Keywords– Articulate Storyline 3, Learning Outcomes, Interactive Learning Media, Conventional Learning